2006
DOI: 10.1016/j.cell.2006.04.029
|View full text |Cite
|
Sign up to set email alerts
|

Histone H2B Monoubiquitination Functions Cooperatively with FACT to Regulate Elongation by RNA Polymerase II

Abstract: Over the past years, a large number of histone posttranslational modifications have been described, some of which function to attain a repressed chromatin structure, while others facilitate activation by allowing access of regulators to DNA. Histone H2B monoubiquitination is a mark associated with transcriptional activity. Using a highly reconstituted chromatin-transcription system incorporating the inducible RARbeta2 promoter, we find that the establishment of H2B monoubiquitination by RNF20/40 and UbcH6 is d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

37
661
4
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 652 publications
(704 citation statements)
references
References 65 publications
37
661
4
2
Order By: Relevance
“…Thus, while carrying out its regular enzymatic activity in the DDR context, it was presumably physically and functionally detached from its regular context. In the transcription context, H2B monoubiquitylation in yeast and mammals is dependent on the early steps in transcription initiation and elongation, and the corresponding E3 ligase closely interacts with many proteins that take part in this process, some of which associate directly with RNA Pol II [41,[49][50][51][52][53][54]99,100]. It is not entirely clear how many of the proteins surrounding RNF20-RNF40 in the transcription context accompany this heterodimer to the DNA damage sites.…”
Section: Rnf20-rnf40 Is Called To Emergency Action Upon Dna Damage Inmentioning
confidence: 99%
“…Thus, while carrying out its regular enzymatic activity in the DDR context, it was presumably physically and functionally detached from its regular context. In the transcription context, H2B monoubiquitylation in yeast and mammals is dependent on the early steps in transcription initiation and elongation, and the corresponding E3 ligase closely interacts with many proteins that take part in this process, some of which associate directly with RNA Pol II [41,[49][50][51][52][53][54]99,100]. It is not entirely clear how many of the proteins surrounding RNF20-RNF40 in the transcription context accompany this heterodimer to the DNA damage sites.…”
Section: Rnf20-rnf40 Is Called To Emergency Action Upon Dna Damage Inmentioning
confidence: 99%
“…In this regard, Fleming et al (2008) found that H2Bub1 plays specific roles in GAL1/10 gene expression in budding yeast, and these roles are independent of its regulation of H3 methylation. In addition, Pavri et al (2006) demonstrated that H2Bub1 directly stimulates FACT (FAcilitates Chromatin Transcription)-mediated transcription using an in vitro chromatin-based transcription system. The ubiquitin moiety of histone H2B is removed by the deubiquitylases, UBP8 and UBP10 (Weake and Workman 2008).…”
mentioning
confidence: 99%
“…FACT recruitment results in nucleosome remodeling making the H2A/B dimer accessible for BRE1A ubiquitination. FACT can in turn directly or indirectly recruit BRE1A complex (RNF20/40) facilitating ubiquitination of H2B‐Lys120 29, 30. In agreement with this, FACT is required in vivo30 for BRE1A/B localization to chromatin in DNA damage responses.…”
mentioning
confidence: 56%